2019
DOI: 10.1111/jfpe.13104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen protection on the extraction yield and antioxidant activities of polyphenols by ultrasonic‐assisted extraction from rapeseed meal

Abstract: It has been found that ultrasonic-assisted extraction (UAE) can dramatically increase extraction yield of polyphenols from raw materials. However, the free radical formation induced by ultrasound will cause a series of oxidation reactions, which may reduce the antioxidant activities of polyphenols. To minimize the oxidation effect produced by ultrasound and increase the biological activities of polyphenols, ultrasonic-assisted nitrogen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…All reagents were prepared according to Ding, Jiang, et al. (2019) with some modifications. FRAP reagent was prepared by adding 25 ml of 300 mM acetate buffer (pH 3.6) with 2.5 ml of 10 mM 2,4,6‐tripyridyl‐S‐triazine (TPTZ) solution (in 40 mM HCl) and 2.5 ml of 20 mM FeCl 3 .6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…All reagents were prepared according to Ding, Jiang, et al. (2019) with some modifications. FRAP reagent was prepared by adding 25 ml of 300 mM acetate buffer (pH 3.6) with 2.5 ml of 10 mM 2,4,6‐tripyridyl‐S‐triazine (TPTZ) solution (in 40 mM HCl) and 2.5 ml of 20 mM FeCl 3 .6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen is an inert gas that could replace atmospheric oxygen in the extraction system and interrupt oxygen‐induced oxidation to protect plant polyphenols. From the sustainability point of view, it is also worth mentioning that the nitrogen could be recycled during the extraction process and reused for further extractions (Ding et al ., 2019). Similar results in the extraction of polyphenols were also observed in other Mediterranean plants such as rosemary and wild thyme (Nutrizio et al ., 2020a,c).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic technology has been widely applied in the research field of natural plant extraction. Ding et al [60] found that ultrasonic extraction could significantly improve the extraction rate of polyphenols from rapeseed meals, but it would cause a series of oxidation reactions that might reduce the antioxidant properties of polyphenols. Therefore, nitrogen protection was necessary to assist the extraction.…”
Section: Ultrasonic Extraction Methodsmentioning
confidence: 99%